The Wonder of Delays - Vazquez, Alexandra T. (Current Musicology, 2018)
There are many things feminist music critics must too often defer by force or by choice. There is so much work and time involved in the mere fact of saying: there is more to the story. In the Latinate New York world, trying to tell a different story—any shift in its form or its players—has long borne challenges that might or might not be particular to it. Some of them have long been archival, at least before YouTube, which has meant having to enter the difficult underworld of possessive collectors. The view from the shore, the view from the dance floor, the dancing mind and thinking body, are made decorative for rather than mutually formative forces to music making. Market and marketing sense and nonsense have given too many empirical shelters from hard thinking about how music is lived and breathed in the social. And the narratives that are made from all this fodder—the wedging of musicians and genres into neat arcs—has meant that we’ve long foregone historical accuracy so that the story tells success in some way. For example, Fania Records: sure, body-rocking objects that trained many of us as listeners and dancers and thank heavens, truly, for that and them. We needed our Motown too. We often desire some sense of success at any cost so that we can make provisional sense of all those lives as they’ve tried to survive here. But Fania Records. That corrupt boys club, which did much to privilege the sloppy musicality of the bro jam band, pernicious in its business practices and misogyny, ruthless on who and how it was able to exclude and start the record of Latin New York in a false place. Fania-as-narrative, or better put, entrepreneurial practice, is just one of the many distractions that have closed up our ears. I’m already distracted. Note the compulsive habit, the getting mad that prevents another kind of work. Let’s get to, and celebrate loud and now, the raptor-like intensity of not being distracted that is Licia Fiol-Matta’s The Great Woman Singer. By creating the complex badass ensemble of Myrta Silva, Ruth Fernandez, La Calandria, and Lucecita, Fiol-Matta asks us: what if we start here? What if we begin with the presumption of women’s musical activity rather than from that shorthanded place of negation? A place that doesn’t begin with how women entered, but made possible, the larger musical scene. This place, the beautiful migrant non-place of this book, goes straight for the historical fact of women in music, but also suggests how criticism (as a whole) has never been able to make this presumption ordinary to talk about them in a sustained, rather than corrective way. What links these performers is their multi-decade careers—which means that we get to follow them from girlhood to golden age. The robust longevity of these musicians, of women who made and make things in colonial modernity, suggests that we have to refigure just about everything that we think we know about the culture industry. Of the wonder of Lucecita and her bendy artistry of the mid-1960s, Fiol-Matta writes: “She had arrived at the scene, but she could not be interpreted yet” (184). I love this delay that the author leaves for herself and for all us here to say: these musicians require time and new words and worlds. Let’s get behind the music of this book and imagine what might be involved in that delay—the work required—to make new tools to interpret these musicians. First, she had to get this group together. Fiol-Matta hosts the musician’s gathering of our dreams, the kind we imagine and hear about that took and take place in people’s living rooms. She makes a cohort where people falsely think there is none and makes the chapters and their players resonate. They are echolocational. Along with this group there is the voluminous matter of their varied entourages. Fiol-Matta tracks and notes all the players, promoters, producers, press agents, and fans that stopped by the musician’s respective careers, and given the decades and publics they did and didn’t share, hurts in its analytic immeasurability. There are the wonderful delays made by archives, official and not, that soak her pages with all sorts of sensate information. Fiol-Matta raises a righteous fist reminder to her readership to say: the Internet is not enough! We still need to talk to people, to interview the seemingly marginal, to go there. There are stunning photographs in the book that leave one imagining the real charm involved in getting permission for them, because these transactions aren’t always about financial compensation. Talking to people carries galaxies of delays. What the original interviews that Fiol-Matta conducted as the book’s grounds don’t easily reveal are the difficult logistics, affective and otherwise, of getting them to sit down and talk. We’ll also want to hold a moment of silence for all those untold hours of preparation and homework for that sitting down and talking. And finally, there is the delay involved at daring to tread in the dizzying undertow of midcentury Puertoricanhood stretching from the 50s to the 70s, with the rise, fake summits, and evaporation of what Fiol-Matta calls the “modernization fantasy” (173), all mobilized by the cold war program, whether operation serenity or bootstrap. In the midst of all this, Fiol-Matta and her book insist on wait-we’re-just-getting-started: we still have our/their records. Her hyper-fluency in the repertoires of these great women singers enables Fiol-Matta to deploy songs as historic signposts, as micro-things that give way to imagining the connectivity between music and musicians across the hispanophonic Caribbean, which we recognize as New York and Mexico City and Havana, but also following Fiol-Matta’s cue: Ponce, Caguas, Arecibo. Songs are followed as indexes for the deep conceptual shifts in music made possible by these singers. Fiol-Matta employs another kind of bilingualism here—one that is fluent in both the highly commodified greatest hit and the underheard, undersold track. Her engagement with these repertoires—across genres, and in an incredible diversity of performance venues—is the training we all need for listening to “salsa,” that mercantile but nonetheless feel-good genre, that can and can’t contain the sounds by and for the multitudes. “Salsa” comes after many befores instituted by the book’s players. And so Fiol-Matta went to where many choose to live but few dare to write into words: those inter-American variety shows that featured this cohort of performers in their late-stage careers. Across all these stages, Fiol-Matta extends the real, material prior behind all those figures that we’re handed as icons without knowing why. This book is an investigation that doesn’t refuse that wonder of childhood not knowing why. All this gives the reader more air and piqued curiosity, and makes one actually want to listen along, to scour YouTube. But even in YouTube, the author manages major surprises. For example, listening and watching along with Fiol-Matta to Lucecita and superCuban percussionist Cándido Camero play together, like that (go there), on the Ed Sullivan show 1970. How did that performance happen? And now, what do we have? I ask that as an honest question, and yes, I’ll retain the we and the possessive not to enclose or exclude, but to long-term honor of the song innovators of The Great Woman Singer. And now, what do we have? is another way of asking: where are they now, how to they show up (and they do) in a place like Spanish trap, for instance? In some ways, the hardest questions Fiol-Matta asks over and over again in her book are: where are they, where are we? She shows us not how to answer these questions because that would suggest the possibility of some singular experience. Instead The Great Woman Singer gives us the ample material evidence and imaginative know-how to extend women’s vocal influence to record all kinds of different stories.